DISKRIMINASI RASIAL DALAM NOVEL â€œKEIN SCHNAPS FÃœR TAMARAâ€ KARYA HANSJÃ–RG MARTIN - JELITA, KRISTINA (UNIVERSITAS NEGERI SURABAYA, 2016)
This research about Racial Diskrimination by Hansjörg  Martin focuses on three matters; 1) how subalternfigure in the novel “Kein Schnaps f?r Tamara” by Hansjörg  Martin; 2) how the form of racial discrimination  that appear in the novel “Kein Schnaps f?r Tamara” by Hansjörg  Martin; 3) which consequence that can be as a result of that racial discrimination. Based on these matters, it could be concluded that this research’s purposes are to describe subaltern in the novel “Kein Schnaps f?r Tamara” by Hansjörg  Martin, to describe the form of racial discrimination that found in the novel “Kein Schnaps f?r Tamara” by Hansjörg  Martin, to describe  the consequence of racial discrimination in the novel “Kein Schnaps f?r Tamara” by Hansjörg  Martin. this research is qualitative research with the descriptive analysis method. Source of the data is the novel “Kein Schnaps f?r Tamara” by Hansjörg  Martin. The data that are looked for consist of words, phrases, sentences which showing about the racial discrimination. The data are collected by using documents technique. The result of this research indicated that (1) the subalternfigure in the novel “Kein Schnaps f?r Tamara” by Hansjörg  Martin is Tamara, that unuseful,  get unfear treatment; (2) the form of racial discrimination in the novel “Kein Schnaps f?r Tamara” by Hansjörg  Martin are refusal and isolation, restriction of freedom, pressing or threat and violence; (3) the consequence of racial discrimination in the novel “Kein Schnaps f?r Tamara” by Hansjörg  Martin are dying, limited the acces, and suppressed the feelling suppressed. Keywords : poscolonial, subaltern and rasial discrimination